Between Firm Changes in Earnings Inequality: The Dominant Role of Industry Effects - John C. Haltiwanger; James R. Spletzer (Institute of Labor Economics (IZA), 2020)
We find that most of the rising between firm earnings inequality that dominates the overall increase in inequality in the U.S. is accounted for by industry effects. These industry effects stem from rising inter-industry earnings differentials and not from changing distribution of employment across industries. We also find the rising inter-industry earnings differentials are almost completely accounted for by occupation effects. These results link together the key findings from separate components of the recent literature: one focuses on firm effects and the other on occupation effects. The link via industry effects challenges conventional wisdom.
Keywords: J3; 330; inequality; industry; occupation